Remarks on the Tithonian-Berriasian ammonite biostratigraphy of west central Argentina - Riccardi, Alberto Carlos (2015)
Status and correlation of Andean ammonite biozones are reviewed. Available calpionellid, nannofossil, and radiolarian data, as well as radioisotopic ages, are also considered, especially when directly related to ammonite zones. There is no attempt to deal with the definition of the Jurassic–Cretaceous limit. Correlation of the V. mendozanum Zone with the Semiforme Zone is ratified, but it is open to question if its lower part should be correlated with the upper part of the Darwini Zone. The Pseudolissoceras zitteli Zone is characterized by an assemblage also recorded from Mexico, Cuba and the Betic Ranges of Spain, indicative of the Semiforme–Fallauxi standard zones. The Aulacosphinctes proximus Zone, which is correlated with the Ponti Standard Zone, appears to be closely related to the overlying Windhauseniceras internispinosum Zone, although its biostratigraphic status needs to be reconsidered. On the basis of ammonites, radiolarians and calpionellids the Windhauseniceras internispinosum Assemblage Zone is approximately equivalent to the Suarites bituberculatum Zone of Mexico, the Paralytohoplites caribbeanus Zone of Cuba and the Simplisphinctes/Microcanthum Zone of the Standard Zonation. The C. alternans Zone could be correlated with the uppermost Microcanthum and “Durangites” zones, although in west central Argentina it could be mostly restricted to levels equivalent to the “Durangites Zone”. The Substeueroceras koeneni Zone ranges into the Occitanica Zone, Subalpina and Privasensis subzones, the A. noduliferum Zone could be equivalent to the Dalmasi Subzone, Occitanica Zone, to lower part of the Boissieri Zone, and the S. damesi Zone could range through the upper part of the Boissieri Zone to the lower part of the Pertransiens Zone. Division of the Substeueroceras koeneni Zone and a precise correlation between the Andean ammonite zones and the international standard require new systematic and stratigraphic studies.